2021
DOI: 10.3390/nu13020527
|View full text |Cite
|
Sign up to set email alerts
|

High β-Glucan Barley Supplementation Improves Glucose Tolerance by Increasing GLP-1 Secretion in Diet-Induced Obesity Mice

Abstract: The aim of this study was to investigate the underlying mechanism for the improvement of glucose tolerance following intake of high β-glucan barley (HGB) in terms of intestinal metabolism. C57BL/6J male mice were fed a fatty diet supplemented with HGB corresponding to 5% of dietary fiber for 83 days. An oral glucose tolerance test was performed at the end of the experimental period. The concentration of short-chain fatty acids (SCFAs) in the cecum was analyzed by GC–MS (gas chromatography–mass spectrometry). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…Through the GPRs on the surface of intestinal endocrine cells, SCFAs promote the secretion of intestinal hormones, such as glucagon-like peptide-1 (GLP-1) and peptide tyrosine tyrosine (PYY; Zhang et al, 2019a;Ren et al, 2020;Wang et al, 2020;Nishida et al, 2021). In particular, GLP-1 enhances glucose tolerance and regulate metabolism (Suzuki and Aoe, 2021), whereas PYY increases satiety, reduces food intake, regulates intestinal movement and slows down gastric emptying to improve body metabolism (Freire and Alvarez-Leite, 2020;Nishida et al, 2021). GPRs affect the influence of gut microbiota on the body's energy, i.e.…”
Section: Metabolismmentioning
confidence: 99%
“…Through the GPRs on the surface of intestinal endocrine cells, SCFAs promote the secretion of intestinal hormones, such as glucagon-like peptide-1 (GLP-1) and peptide tyrosine tyrosine (PYY; Zhang et al, 2019a;Ren et al, 2020;Wang et al, 2020;Nishida et al, 2021). In particular, GLP-1 enhances glucose tolerance and regulate metabolism (Suzuki and Aoe, 2021), whereas PYY increases satiety, reduces food intake, regulates intestinal movement and slows down gastric emptying to improve body metabolism (Freire and Alvarez-Leite, 2020;Nishida et al, 2021). GPRs affect the influence of gut microbiota on the body's energy, i.e.…”
Section: Metabolismmentioning
confidence: 99%
“…Increased GLP-1 secretion in the OGTT may be due to increased L-cell counts in the ileum. In our previous study data indicated that high β-glucan barley consumption increased ileal NeuroD and cecal GLP-1 pool size [ 26 ]. The current study shows similar results, suggesting that barley-derived arabinoxylan may also increase L-cell numbers by increasing SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that barley consumption improves blood lipid parameters and glucose tolerance. [6][7][8][9][10] In general, these effects are thought to be due to the increased viscosity of digesta by β-glucan in the digestive tract, forming a gel that reduces the rate of other nutrient absorption. 7 This enhanced viscosity inhibits postprandial glucose spikes and excess insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that mice fed barley contained high-β-glucan levels displayed improved glucose tolerance via increasing L-cell counts and enhanced GLP-1 secretion. 9 Another study reported that mice fed barley flour improved insulin sensitivity via SCFAs, which promote the secretion of intestinal hormones such as GLP-1. 10 However, both studies did not examine the effects of GPR43.…”
Section: Introductionmentioning
confidence: 99%